Contributions to the knowledge of the Staphylinus-complex (Coleoptera: Staphylinidae: Staphylinini) of China. Part 21. The genus Ocypus Leach, 1819, subgenus Pseudocypus Mulsant & Rey, 1876. Section 4 - Smetana, Aleš (Zootaxa, 2009)
The paper deals with the species of the picipennis- and fuscatus-lineages of the subgenus Pseudocypus Mulsant & Rey, 1876 of the genus Ocypus Leach, 1819, known to occur at present on the territory of the People’s Republic of China, in the Russian Far East, and in Japan. Eight species are treated, all previously described: O. picipennis (Fabricius, 1793), O. helleni (J. Müller, 1926), O. aenescens Eppelsheim, 1889, O. inexspectatus Eppelsheim, 1887, O. shiretokensis Hayashi, 2008, O. graeseri Eppelsheim, 1887, O. fuscatus (Gravenhorst, 1802) and O. nigroaeneus Sharp, 1889. Based on the study of the type material, the following new synonymies are proposed: Staphylinus (Pseudocypus) rambouseki J. Müller, 1925 and Pseudocypus fuscatoides Coiffait, 1964 are placed in synonymy with Ocypus (Pseudocypus) graeseri Eppelsheim, 1887. Ocypus eppelsheimi Reitter, 1887 is transfered to the genus Miobdelus Sharp, 1889 (comb. nov.); Miobdelus montivagus Smetana, 2001 becomes a junior objective synonym of it (syn. nov.). Lectotypes are designated for Ocypus helleni, Ocypus rambouseki, Ocypus nigroaeneus and Ocypus eppelsheimi. Neotype is designated for Ocypus graeseri Eppelsheim, 1887. Each species is described, illustrated and all available distributional and bionomic data are given. A key to the species of the picipennis- and fuscatus-lineages of the subgenus Pseudocypus, that occur in People’s Republic of China, in the Russian Far East, and in Japan, is given.